The Structure of Southwest Taiwan: The Development of a Fold‐and‐Thrust Belt on a Margins Outer Shelf and Slope. Issue 7 (16th July 2018) - Biete, Cristina; Alvarez‐Marron, Joaquina; Brown, Dennis; Kuo‐Chen, Hao
Abstract: The southwest Taiwan fold‐and‐thrust belt is forming on the outer shelf and slope of the Eurasian continental margin. It comprises a roughly N‐S striking, west verging imbricate thrust system that has been developing since the Late Miocene. Here we present the results of new surface geological mapping from which we construct balanced and restored cross sections and along‐strike sections. From these we compile maps of the basal thrust, thrust branch lines and, where possible, stratigraphic cutoffs. To interpret the structure in the subsurface and beneath the basal thrust, we use a P wave velocity of 5.2 km/s as a proxy for the top of the Mesozoic basement. We divide the southwest Taiwan fold‐and‐thrust belt into a number of thrust sheets that form the basis of our description and interpretations. From these data we interpret the 3‐D structure of the fold‐and‐thrust belt and the influence that the structure and morphology of the continental margin is having on its development. We show that there is a significant along‐strike change in the structure. This change takes place across a transverse zone that is composed of a suite of structures at the surface. We suggest that this transverse zone has a causal relationship with variations in the geometry of the basal thrust which in turn is related to (possibly fault bounded) basement highs and lows that are inherited from the continental margin. Plain Language Summary: The southwest Taiwan fold‐and‐thrust belt comprises a roughly N‐S striking, west verging imbricate thrust system that has been developing since the Late Miocene. We present the results of new surface geological mapping from which we construct balanced and restored cross sections and along‐strike sections. We compile maps of the basal thrust, thrust branch lines, and stratigraphic cutoffs. We divide the southwest Taiwan fold‐and‐thrust belt into a number of thrust sheets that form the basis of our description and interpretations. From these data we interpret the 3‐D structure of the fold‐and‐thrust belt and the influence that the structure and morphology of the continental margin is having on its development. We show that there is a significant along‐strike change in the structure. This change takes place across a transverse zone that is composed of a suite of structures at the surface. We suggest that this transverse zone has a causal relationship with variations in the geometry of the basal thrust which in turn is related to (possibly fault bounded) basement highs and lows inherited from the continental margin. Key Points: Structure of the fold‐and‐trust belt in southwest Taiwan Development of a fold‐and‐thrust belt on the outer continental margin and slope Along‐strike changes in structure that have a causal relationship with variations in the basal thrust that, in turn, is related to basement